Noisy vestibular stimulation improves body balance in bilateral vestibulopathy - Iwasaki, Shinichi; Yamamoto, Yoshiharu; Togo, Fumiharu; Kinoshita, Makoto; Yoshifuji, Yukako; Fujimoto, Chisato; Yamasoba, Tatsuya (Neurology, 2014)
To examine the effect of an imperceptible level of galvanic vestibular stimulation (GVS), delivered as zero-mean current noise (noisy GVS), on postural performance in healthy subjects as well as in patients with bilateral peripheral vestibular dysfunction. White noise GVS with an amplitude ranging from 0 to 1,000 μA was applied in 21 healthy subjects and 11 patients with bilateral vestibular dysfunction. Two-legged stance tasks were performed with the eyes closed during a 60-second period, which consisted of a baseline period without stimulation and a stimulation period with GVS. We examined 3 parameters: the velocity, the envelopment area, and the root mean square (RMS) of the center of pressure. White noise GVS improved all 3 parameters in 76% of healthy subjects. The amplitude of the optimal stimulus was 281 ± 40 μA, and it improved the velocity, area, and RMS by 18.4% ± 2%, 37.9% ± 3.5%, and 20.4% ± 2.2%, respectively (p < 0.01). The GVS improved all 3 parameters in 91% of patients. The amplitude of the optimal stimulus was 456 ± 82 μA, and it improved the velocity, area, and RMS by 29.4% ± 4.9%, 45.6% ± 4.7%, and 22% ± 3.3%, respectively (p < 0.01). Noisy GVS is effective in improving postural stability in healthy subjects as well as in patients with bilateral vestibular dysfunction. This study provides Class IV evidence that in patients with bilateral vestibular dysfunction, an imperceptible level of noisy GVS may improve postural stability.